Analysis Entrepreneurial Characteristic that Supports Culinary Entrepreneurs to Survive During Covid-19 Pandemic - Aristo Surya Gunawan; Ati Cahayani (Syntax Corporation, 2023)
During COVID-19 pandemic, almost all economic sector in Indonesia fell. Accommodation, food and beverage (culinary) sectors were the third largest industry after the manufacturing and construction industry, which laid off workers. There was one interesting point, in this pandemic storm MSMEs were affected quite badly compared to the economic crisis hit in late 90s. Another interesting point was that some of MSMEs suffered from profit decrease to loss and even bankruptcy. However, some MSMEs could survive. What makes them survive? Through researchers observation, we saw that culinary entrepreneurs as respondents consider some behaviors to be the key to their business survival during the pandemic. Based on theory these behaviors are considered as entrepreneurial characteristics. The research objective of this article is to test confirmation among respondents that entrepreneurial characteristic is the key to survival regarding the demographic and experience factors. This research used a descriptive quantitative method and Levane’s test for equality of variances. As the result respondents showed no differences based on their demographic and experience factors to see that entrepreneurial characteristics is the key of their survival during the pandemic.